Aesthetic Reflection in the Condolence Poetry for the Death of Abul-Ala’i (By Late Nigerian Grand Literati Muhammad Al-Ghali Kabara) - Kabara, Ishaq Abubakar (LANGUAGE ART, 2020)
This research addresses descriptive of artistic work named; the condolence poetry for the death of Abul-Ala’i, by Late Nigerian grand literati Muhammad Al-Ghali. The research deals with an explicit analysis of literary beauties, emotions, feelings, verbal ornament, and comment about the exclamation and psychological nature facing the poet. The paper reached conclusion that; the method used by the Literati Muhammad Al-Ghali in his condolence poetry concerned to convey this thoughts and create his imaginative world, and it worth mentioning the Literati on way will be clear and to shows his ability to use language to highlight his know-how, furthermore the poet performed to identified his emotion and feelings of sadness of the death.